Effects of Zn Interlayer and Welding Current on the Mechanical Properties of TIG Welded 7075 Al Alloy - S. Abbas, Waseem; Alali, M.; H. Abbas, Mohammed (International Journal of Engineering and Technology, 2018)
Gas tungsten arc welding of AA7075 Al alloy with ER4043 filler metal and Zn interlayer was carried out. The Zn foil was added to the fusion zone to improve the mechanical properties of the weld and minimise the difficulties associated with fusion welding of AA7075 Al alloy. The tensile shear property and the hardness of the weld were investigated as a function of welding current. Results show that a free-crack weld was obtained in the whole samples. Welding current of 90A showed the highest weld shear strength and hardness. Generally, the weld shear strength recorded a 76% to 86% from the tensile strength of the base metal and the highest hardness reached 75% from the base metal. This study aims to improve the capability of cheaper and more versatile fusion welding of Al alloy over the solid-state welding.Â Â